UHPLC-QTOF-MS/MS-based metabolomic discovery of anticancer compounds in ethanolic extracts of Ficus hispida L. f. - Saengrawee Thammawithan; Jirattiporn Thanuma; Sirinya Sitthirak; Chadapohn Panplu; Thapanee Pruksatrakul; Piya Prajumwongs; Arporn Wangwiwatsin; Poramate Klanrit; Watcharin Loilome; Nisana Namwat (PLoS ONE, 2026)
Ficus hispida L. f. ( F. hispida ) is commonly used in traditional medicine for various health problems. No comprehensive analysis of all its components has yet been undertaken, despite researchers having explored its chemical constituents and biological activities. Using untargeted metabolomics, we aimed to assess the chemical compositions and metabolic differences among the five parts of F. hispida : bark, fruits, leaves, twigs, and stalks. To discover the compounds that might be accountable for the noted efficacy, our study assessed the correlation between the identified metabolites and anticancer activities. We applied untargeted metabolomics using UHPLC-QTOF-MS/MS to confirm a total of 82 metabolites. These compounds were classified into six phytochemical groups with predominant accumulation in each part: fatty acids and their conjugates (twigs), terpenoids (stalks), phenylpropanoids (bark and twigs), alkaloids (bark and leaves), saccharides and their conjugates (bark), and amino acids and peptides (twigs and stalks). Multivariate analysis showed markedly distinct metabolic patterns across the five tested parts, especially leaf and bark extracts. The sulforhodamine assay (SRB) for the cytotoxicity test revealed that the bark and leaf extracts had the highest potential to inhibit the viability of cholangiocarcinoma (CCA) cells, with IC 50 values of 0.71 ± 0.17 µg/mL and 0.82 ± 0.22 µg/mL for KKU-213A, and 0.78 ± 0.13 µg/mL and 1.03 ± 0.21 µg/mL for KKU-055. Univariate analysis revealed that four metabolites, including catharanthine, cianidanol, procyanidin B2, and quinic acid, had significant correlation with these anticancer abilities. Subsequent cytotoxicity studies on these candidate metabolites revealed that catharanthine suppressed CCA cell viability at the IC 50 of 41.0 ± 0.99 µM (KKU-213A) and 47.4 ± 4.34 µM (KKU-055) over other candidates. Our research suggests that catharanthine, which is a terpene indole alkaloid found in the bark and leaves of F. hispida, is responsible for the anticancer efficacy against CCA cells.